2011
DOI: 10.1016/j.tet.2011.06.106
|View full text |Cite
|
Sign up to set email alerts
|

Imidazo-benzo-15-crown-5 ethers bearing arylthienyl and bithienyl moieties as novel fluorescent chemosensors for Pd2+ and Cu2+

Abstract: a b s t r a c tNovel fluorescent ionophores bearing imidazo-arylthienyl or imidazo-bithienyl p-conjugated bridges functionalized with one or two fused benzo-15-crown-5 ethers as receptor units are reported. The sensing ability of the compounds in the presence of metallic cations (Li þ , Na þ , K þ , Ca 2þ , Zn 2þ , Cu 2þ , Ni 2þ , Pd 2þ , and Hg 2þ ) and fluoride ion was studied in MeCN/DMSO solutions by absorption and emission spectroscopy. The experimental results indicate that all compounds could act as sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…51 In addition, they are also used as optical chemosensors in organic solvents and aqueous solutions, and as bioimaging probes for the detection of anions, neutral molecules and metal ions with biological/medical relevance. 49,[52][53][54][55][56][57][58][59][60][61] Several imidazole derivatives have been used as pH sensors. Ge et al reported the synthesis of a 4-phenyl-pyrido[1,2-a] benzimidazole-3-carboxylic acid (PPBI-1), which exhibits a uorescence quantum yield of 0.96 and is sensitive to pH values between 4.2 and 6.4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 In addition, they are also used as optical chemosensors in organic solvents and aqueous solutions, and as bioimaging probes for the detection of anions, neutral molecules and metal ions with biological/medical relevance. 49,[52][53][54][55][56][57][58][59][60][61] Several imidazole derivatives have been used as pH sensors. Ge et al reported the synthesis of a 4-phenyl-pyrido[1,2-a] benzimidazole-3-carboxylic acid (PPBI-1), which exhibits a uorescence quantum yield of 0.96 and is sensitive to pH values between 4.2 and 6.4.…”
Section: Introductionmentioning
confidence: 99%
“…Following our previous work on imidazole derivatives for various optoelectronic and biological applications, [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] along with OIH materials for concrete sensing, 66,67 the current work reports the synthesis of an imidazole derivative and the characterization of OIH materials, pure and doped with the uorescent triarylimidazole, to evaluate the prospect of preparing pH-sensitive membranes for use in OFS to evaluate the carbonation of concrete. The synthesised OIHs were based on Jeffamine® THF170 and 3-glycidoxipropyl-trimethoxysilane, which showed suitable properties for the desired application in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…1. Although the N-phenylaza-15-crown-5 compounds are well known to recognize sodium, potassium, calcium, lead and mercury ions [7, 8]; our compound only selective mercury ion. So, a shift in absorption band could not be observed in these experiments except for mercury (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…306 These compounds have been widely reported in the design of fluorescent metal sensors. 103,302,307 For instance, in 2017 Li et al published a very interesting and detailed review, which focused on the main advances and achievements in the design of crown ethers containing fluorescent probes and their applications in biological systems. 103 Therefore, and considering the information already published, this review will focus only on the use of crown ethers reported in OFS for K + and Na + detection in biological and non-biological samples.…”
Section: Ofs For K + and Na + Detectionmentioning
confidence: 99%